The effect of different dose of heparin using in peripheral arteriovenous synchronous blood exchange transfusion for neonatal hyperbilirubinemia: Effect of Heparin Dose in Neonatal Hyperbilirubinemia Treatment - Guan, Xueyun; Guo, Jing; Xiao, Dongsu; Wu, Zhong (Journal of Medical Biochemistry, 2023)
Background: To explore the optimal dosage of heparin in peripheral arteriovenous automatic synchronous exchange transfusion therapy for neonatal hyperbilirubinemia. Methods: A total of 185 neonates received peripheral arteriovenous synchronous blood exchange transfusion for hyperbilirubinemia were enrolled from pediatric department of the Ganzhou People's Hospital between January 2018 and June 2020, which were randomly divided into four groups. On the basis of exchange transfusion, different dose of heparin was pumping at the bleeding site of artery (A: no heparin; B: 100 U/h heparin; C: 200 U/h heparin; D: 300 U/h heparin). The indexes of exchange transfusion efficacy, including total bilirubin conversion rate, indirect bilirubin conversion rate, hemoglobin concentration, the platelet number and APTT value was measured before and after therapy. The sites of artery puncture, the sites and rate of vascular occlusion were counted and analyzed. Results: There was no significant difference for total bilirubin conversion rate, indirect bilirubin conversion rate, hemoglobin concentration platelet number and APTT value before and after exchange transfusion between the four groups (P >0.05). In addition, there was no statistical significance in artery puncture sites between the four groups (P > 0.05). Significant difference in total rate of vascular occlusion and rate of radial artery occlusion were found between the four groups (P< 0.05). Conclusion: Different dose of heparin using in peripheral arteriovenous synchronous blood exchange transfusion did not affect the therapeutic effect or coagulation function of patients, but could reduce the rate of occlusion depending by the site of arterial puncture.